Cationic starches in paper-based applications—A review on analytical methods. (1st May 2020) - Chemelli, Angela; Gomernik, Florian; Thaler, Ferula; Huber, Anton; Hirn, Ulrich; Bauer, Wolfgang; Spirk, Stefan
Highlights: Review with more than 100 references on cationic starches. Overview on industrially relevant cationic starches. Summary on analytical techniques for cationic starches. Identification of challenges in the analysis of cationic starches. Abstract: This review focuses on cationic starches with a low degree of substitution (<0.06) which are mainly used for production of paper-based products. After a brief introduction on starch in general, cationization pathways and importance of cationic starches in paper production, this review emphasizes on the analytical challenges from different perspectives. These include the different length scales of starches when in solution: the macromolecular level, their assembly into nm aggregates and finally hydrocolloids with hundreds of nanometers of diameter. We give an overview on the current state of the art on the analysis of such challenging samples and aim at providing a guideline for obtaining and presenting reliable analytical data.